Hepatothoracic transits of hydatid origin: personal experience on 11 cases - Praderi, Luis A; Cassinelli, Daniel (Cirugía del Uruguay, 2021)
In this paper the clinic, pathology and treatment of a series of 11 cases of right hepatopleuropulmonary transits of hydatid origin are analyzed. Its frequency is believed to be a 3,9 % ir;_ a general surgery Service. In the clinical study there is a· marked predominance of the thoracic over the abdominal symptomatology. Simple and , contrasted radiological studies should be ádapted to the circumstances of each case. The anatomical types correspond to closed hepatopleural, 1; closed hepatopulmonary, 1; · hepatobronchial, 3; hepatopleuralbronchial, 3; and three cases are described of transits during the postoperatory period of hepatic cystoctomies and cystectomies due to a probable failure in the diaphragmatic suture. After analyzing indications of urgency, approach and operatory tactics, the authors insist in the advantages of economic resections in lung and liver. This series had a good evolution, with one death due to heart failure.